Perancangan Sistem Kendali Pengaturan Pemberian Larutan Nutrisi pada Tanaman Hidroponik Berbasis Arduino - Hafid Krisna Wahyu Wijaya, Muhammad; Rhafi Arsyan, Hafid; Seto Adi, Alfian; Pramono (CV. Shofanah Media Berkah, 2024)
An Arduino-based control system for nutrient solution management in hydroponic plants is developed to enhance efficiency and plant quality. The system utilizes sensors to monitor environmental conditions and automatically adjusts pH and nutrient levels in the solution, thereby achieving an optimal environment for plant growth. Consequently, the system can improve crop yields, reduce labor costs, and enhance the efficiency of hydroponic farming practices.